Restrictions of the common bean productivity in direct seeding system in the brazilian cerrado - Freddi, Ona da Silva; Rimoldi Tavanti, Renan Franscisco; Passos e Carvalho, Morel de [UNESP]; Montanari, Rafael [UNESP]; Andreotti, Marcelo [UNESP] (Univ Federal Mato Grosso, 2017)
The productivity of common bean in Brazil is considered low when compared to the productive potential of the cultivars used. Fertility conditions due to surface fertilization, and soil compaction in areas that adopt a direct seeding system, mainly irrigated, may be some of the factors limiting bean development. Thus, the objective of this study was to determine the spatial distribution and correlation of physical and chemical soil properties with the yield of irrigated beans in a direct seeding system. The study was conducted in an Typic Acrustox located in the municipality of Selviria (MS), in the Cerrado biome. To determine properties of the soil and plant, a sampling grid was installed containing 121 points distributed over an area of 1815 m(2). There was variation in soil fertility, limiting bean yield. In places with higher values of pH, sum of bases, V% and organic matter yields were found to be the highest. In places with pH and V% below 4.6 and 34.11%, respectively, yields below 2900 kg ha(-1) were observed. There were places where penetration resistance (PR) of the soil was less than 2 MPa, but also places with RP reaching values of 4.67 MPa, however, without correlation to bean yield.
Keywords: Phaseolus vulgaris L.; agricultural sustainability; principal component analysis; soil fertility; soil compaction